2014
DOI: 10.1111/anu.12105
|View full text |Cite
|
Sign up to set email alerts
|

Influence of digestible protein levels on growth and feed utilization of juvenile meagreArgyrosomus regius

Abstract: This study investigates the effect of digestible protein levels in experimental diets for meagre (Argyrosomus regius). A group of 253 fish, 52 g of mean weight, was distributed in 12 tanks, three replicates per treatment. Four isolipidic diets (170 g kg−1 crude lipid) with different digestible protein levels (350 g kg−1, 430 g kg−1, 490 g kg−1 and 530 g kg−1) were formulated using commercial ingredients. The trial lasted 62 days. Meagre fed diets 430, 490 and 530 g kg−1 obtained higher TGC (2.47, 2.57, 2.69 × … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 54 publications
2
18
1
Order By: Relevance
“…In this study, we also found that increasing the dietary protein or lipid level could improve feed efficiency, with a combination of the two resulting in the best growth. In contrast, high dietary protein (36%) reduced the protein efficiency ratio vs. low dietary protein (24%), as observed in previous studies with fish including tilapia (Lee et al, 2006;Abdel-Tawwab et al, 2010;Cho, 2011;Velazco-Vargas et al, 2014).…”
Section: Discussionsupporting
confidence: 71%
“…In this study, we also found that increasing the dietary protein or lipid level could improve feed efficiency, with a combination of the two resulting in the best growth. In contrast, high dietary protein (36%) reduced the protein efficiency ratio vs. low dietary protein (24%), as observed in previous studies with fish including tilapia (Lee et al, 2006;Abdel-Tawwab et al, 2010;Cho, 2011;Velazco-Vargas et al, 2014).…”
Section: Discussionsupporting
confidence: 71%
“…The voluntary feed intake may change to improve feed use and growth (García‐Meilán, Valentín, Fontanillas, & Gallardo, ). Because fish consume food to satisfy their energy requirement (Chaitanawisuti & Rodruang, ), possibly the range of P/E ratio used in the present study was not enough to provoke significant difference in feed consumption and utilization of Brazilian sardine, as well as in meagre Argyrosomus regius fed to increasing levels of protein (Velazco‐Vargas et al., ).…”
Section: Discussionmentioning
confidence: 90%
“…The dietary protein is broken down into smaller molecules in the gastrointestinal tract, which secrets fluids, electrolytes and digestive enzymes that allow the free amino acids to be absorbed and used (Buddington & Krogdahl, ). A diet that contains protein in excess of fish requirements promotes ammonia excretion and a high use of energy for amino acid catabolism, which can reduce growth rate (Velazco‐Vargas et al., ). On the other hand, low protein dietary content negatively affects fish growth and health.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the body and fillet traits of this large species have shown a very high dressing content with a negligible amount of mesenteric and muscular fat in comparison with other cultured fish that makes this species even more interesting for industrial processing and human consumption (Hernández et al, 2009;Poli et al, 2003). As an emerging species for aquaculture, little information is available on the dietary requirements of meagre, including their amino acid requirements, as well as in the development and optimization of sustainable feeds for maximum growth (Chatzifotis, Panagiotidou, & Divanach, 2012;Chatzifotis et al, 2010;Estévez et al, 2011;Velazco-Vargas et al, 2014).…”
Section: Introductionmentioning
confidence: 99%